Implementation of M-Learning Applications as Learning Media Based on Android - Chandra Kirana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The purpose of this study is to provide benefits to student in the learning process. Currently the learning prcess is still monotonous or manual. Based on the above problems, the researcher wants to make an application as a learning tool based on android. This application contains materials. This application is also equipped with practice questions in accordance with the student’s major. The application of the learning model is one of the duties of the teacher to assist student development in learning outcomes. However, in general student view knowledge as a tool that must be memorized, so a learning model that empowers students is needed, namely a learning model that encourages students to be more active and independent. Therefore, to overcome this problem, an android-based application is needed that can be used in everyday life and as a learning medium that can be used by students to make learning easier through an android based smartphone that students can use as a fun learning medium, and make students more interested. With the android based M-learning application as the latest learning media, it makes the learning process easier. In addition, with this application learning becomes more affective and afficient.